CURRENT AND EMERGING TRENDS IN THE MANAGEMENT OF PYODERMA GANGRENOSUM: A LITERATURE REVIEW - Wali Muhammad, Sobia; Nadia Hassan,; Samra Khan,; Atia Gohar, (Journal of Ayub Medical College Abbottabad, 2024)
The first description of Pyoderma gangrenosum (PG) was made about a century ago. It is difficult to understand the aetiology, pathophysiology, and therapy of PG. This disease is believed to be caused by a systemic inflammatory response to neutrophil chemotaxis and faulty innate immune system control. Nearly fifty percent of the cases have underlying systemic symptoms. Significant improvements in PG management have been made over the years. The main goals of treatment are to reduce inflammation and speed up the healing of the PG wound. Even though the most recent medicines show promise, they are found on isolated case reports. The majority of patients are typically managed with topical treatment and local wound care, while resistant cases necessitate immunosuppressive medications. More progress can be made with improvements in technology in deciphering this complex disease and getting a greater understanding of the condition. The present standard therapies for refractory PG are not well supported by studies. In refractory PG, corticosteroids and cyclosporine have historically been administered. Tumour necrosis factor inhibitors are becoming a viable option; nonetheless, this requires careful research and upkeep. This review intended to describe the current trends in managing the PG. Several next-generation treatment options including the conventional therapies introduced to treat PG. We encompass the advantages and disadvantages of new treatments for PG.